How electron beam melting tailors the Al-sensitive microstructure and mechanical response of a novel process-adapted γ-TiAl based alloy. (15th December 2021) - Wimler, David; Käsznar, Katharina; Musi, Michael; Breuning, Christoph; Markl, Matthias; Keckes, Jozef; Clemens, Helmut; Körner, Carolin; Mayer, Svea
Graphical abstract: Highlights: Establishing the impact of EBM parameters on TiAl microstructure and their mechanical response. Correlation of the experimental results with numeric simulation, regarding the Al evaporation. Discovery of a parameter-dependent solidification structure, masked by two solid-state transitions. Abstract: Additive manufacturing of lightweight intermetallic γ -TiAl based alloys combines process-related freedom of design with material-specific excellent high-temperature properties. Nevertheless, where locally melting the powder by an electron beam, there is a risk that Al evaporates due to its high vapor pressure, causing compositional and microstructural variations. This work investigates the impact of different process parameters on the total and local Al-content as well as the resulting as-built and heat-treated microstructure in a complex multiphase Ti-44.8Al-4.1Nb-0.7W-1.1Zr-0.4Si-0.5C-0.1B (at.%) alloy. The examinations applied are complementary, employing electron microscopy, X-ray spectroscopy and diffraction experiments with synchrotron X-ray radiation, supported by numerical simulations. The mechanical anisotropy of the heat-treated microstructure was analyzed by micro-hardness measurements. The results demonstrate that the amount of γ -TiAl phase decreases with increasing energy input of the electron beam in the as-built and heat-treated microstructure owing to the total and local loss of Al. Besides, the investigations of the crystal orientations within the multiphase alloy reveal a preferred orientation of the γ phase at high energy inputs. This follows from the fact that the preferred γ orientation is inherited through directional solidification of the β phase. The obtained process-microstructure-property relationships show that tailor-made material properties of additively manufactured γ -TiAl components are achievable.